PENGARUH PRODUK DAN HARGA TERHADAP MINAT BELI SERTA KEPUTUSAN PEMBELIAN PADA PT. CITRABANGUN DELTAREKSA - Cloudya, Cloudya; Pranoto, Suryo Budi (SCIENTIA JOURNAL, 2019)
Currently Batam Island is still increasing and continues to increase, business people are finally increasingly trying to innovate which can increase the competitiveness of companies in their business. Companies find the relationship between products and prices,where consumers see products and prices that affect buying interest in consumer purchasing decisions,and the company always tries to provide the best for consumers. The type of research that will be used is quantitative research. The population in this study is housing that is available to consumers as many as 220 people, while the sample used was 142 consumers using the Proportionate Stratified Random Sampling. The results in this study indicate that the t-test of the product and price has a positive and significant influence on buying interest in PT Citrabangun Deltareksa.While the product has a negative and not significant effect on purchasing decisions and prices have a positive and significant influence on purchasing decisions at PT Citrabangun Deltareksa.